(untitled) (Journal of Asian Development Studies, 2015)
The main theme of the research is to discuss the changing scenario of the of the Arab-Yemen conflict. The study focuses on the dynamics of relating issue. It also investigates the facts and role of the international community. The research describes the concerns of the neighbor countries. Pakistan believes in Muslim brotherhood. The study analyses the foreign policy of Pakistan in this context.